The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fmicb.2020.00527
|View full text |Cite
|
Sign up to set email alerts
|

Iron to Gas: Versatile Multiport Flow-Column Revealed Extremely High Corrosion Potential by Methanogen-Induced Microbiologically Influenced Corrosion (Mi-MIC)

Abstract: Currently, sulfate-reducing bacteria (SRB) is regarded as the main culprit of microbiologically influenced corrosion (MIC), mainly due to the low reported corrosion rates of other microorganisms. For example, the highest reported corrosion rate for methanogens is 0.065 mm/yr. However, by investigating methanogen-induced microbiologically influenced corrosion (Mi-MIC) using an in-house developed versatile multiport flow test column, extremely high corrosion rates were observed. We analyzed a large set of carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…The low to moderate corrosion rates in the absence of micH -positive Methanococcus spp. agree with corrosion rates documented for sulfidogenic cultures of D. alaskensis (≤0.1 mm Fe 0 · yr −1 ; [ 22 , 49 , 50 ]). We cannot, however, exclude the possibility that hitherto unknown enzymatic mechanisms may have affected corrosion in our experiments.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The low to moderate corrosion rates in the absence of micH -positive Methanococcus spp. agree with corrosion rates documented for sulfidogenic cultures of D. alaskensis (≤0.1 mm Fe 0 · yr −1 ; [ 22 , 49 , 50 ]). We cannot, however, exclude the possibility that hitherto unknown enzymatic mechanisms may have affected corrosion in our experiments.…”
Section: Discussionsupporting
confidence: 87%
“…Electrochemical studies suggested a mediator-free direct electron uptake mechanism for one of these Fe 0 -utilizing isolates, Methanobacterium -like strain IM1 ( 21 ). The potential technical relevance of this microorganism has been demonstrated in laboratory studies in which strain IM1 was grown in flow-through systems ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…The crust formed by strain IM1 has a domed appearance, similar to MIC crusts formed by sulfate reducers (Venzlaff et al, 2013) rather than to crusts reported for other methanogens (Uchiyama et al, 2010). Under continuous flow systems, strain IM1 formed crusts with less prominent, rather flattened domes (An et al, 2020). Correlation of the EDX-resolved elemental composition with Raman spectra indicated that the crust was composed mainly of calcite and siderite, both commonly formed by corrosive methanogens (Uchiyama et al, 2010;Little et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
“…IM1 under static conditions (0.15 mm/yr) and was as high as the average corrosion rate of Methanobacterium sp. IM1, which was obtained in the flow system of a versatile multiport column filled with carbon steel beads [25]. The accumulation of non-conductive corrosion products, such as siderite formed by methanogenic corrosion, restricts the access of cells or enzymes to the iron surface and results in a lower corrosion rate.…”
Section: Discussionmentioning
confidence: 99%